Rectovaginal fistula in a patient with Mayer-Rokitansky-Kuster-Hauser syndrome - Puvvada Sandeep; S. Shanthakumar; Venkata Mahesh Chalumuru; D. Ramesh; Tarun Dilip Javali (Urology Case Reports)
MRKH syndrome is defined by the congenital absence of the uterus and the upper two-thirds of the vagina in females, who otherwise exhibit normal secondary sexual characteristics and possess a typical 46, XX karyotype. Here we report a case of 23 year old female diagnosed with Mayer-Rokitansky-Kuster-Hauser syndrome when presenting with features of rectovaginal fistula.